2016
DOI: 10.1038/srep31763
|View full text |Cite
|
Sign up to set email alerts
|

Prosteatotic and Protective Components in a Unique Model of Fatty Liver: Gut Microbiota and Suppressed Complement System

Abstract: Goose can develop severe hepatic steatosis without overt injury, thus it may serve as a unique model for uncovering how steatosis-related injury is prevented. To identify the markedly prosteatotic and protective mechanisms, we performed an integrated analysis of liver transcriptomes and gut microbial metagenomes using samples collected from overfed and normally-fed geese at different time points. The results indicated that the fatty liver transcriptome, initially featuring a ‘metabolism’ pathway, was later joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
68
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 61 publications
15
68
2
Order By: Relevance
“…At the genera level, HFD consumption was associated with a higher abundance of Mucispirillum . This result was consistent with previous report . Furthermore, we observed that the ICR interventions significantly increased the species of Fecalibaculum .…”
Section: Discussionsupporting
confidence: 94%
“…At the genera level, HFD consumption was associated with a higher abundance of Mucispirillum . This result was consistent with previous report . Furthermore, we observed that the ICR interventions significantly increased the species of Fecalibaculum .…”
Section: Discussionsupporting
confidence: 94%
“…Considering that long-term stress could reduce the diversity of intestinal microbiota [30], this result may be because the ducks were raised on a net and unable to contact the natural environment. Firmicutes, Bacteroidetes, Actinobacteria and Proteobacteria were dominant in the cecum in both systems, and this result coincides with wild turkeys, captive broilers, caged Beijing ducks and oor-raised Landes geese [31][32][33][34].…”
Section: Discussionsupporting
confidence: 53%
“…Long-term heavy drinking is the main independent risk factor of fatty liver disease[ 25 ], but its pathogenesis is not clearly defined. Liu et al[ 26 ] found that gut microbiota played a synergistic role in the liver response, and the complement system was suppressed in fatty liver which was partially due to increased blood lactic acid from enriched Lactobacillus. Abnormal complement activation reportedly enhances the sensitivity of steatotic livers to ischemia and reperfusion injury, which leads to the development of fatty liver[ 27 , 28 ].…”
Section: Complement Activation In Aldmentioning
confidence: 99%